Hydrogen Sulfide Signaling Protects Chlamydomonas reinhardtii Against Allelopathic Damage From Cyanobacterial Toxin Microcystin-LR - Chen, Xiao-Dong; Liu, Yue; Yang, Li-Ming; Hu, Xiang-Yang; Jia, Ai-Qun (Frontiers in Plant Science, 2020)
Cyanobacterial blooms have become more frequent and serious in recent years. Not only do massive blooms cause environmental pollution and nutrient eutrophication, but they also produce microcystins (MCs), a group of toxic cycloheptapeptides, which threaten aquatic ecosystem and human health. As such, clarifying the allelopathic interactions between cyanobacteria and other algae is critical to better understand the driving factors of blooms. To date, however, such studies remain largely insufficient. Here, we treated model alga Chlamydomonas reinhardtii with microcystin-LR (MC-LR) to determine its allelopathic effects. Results showed that MC-LR markedly suppressed C. reinhardtii cell viability. Comparative proteomic and physiological analyses revealed that MC-LR significantly up-regulated protein abundance of antioxidants ascorbate peroxidase (APX) and catalase (CAT) at the beginning stage of exposure. This was accompanied by an over-accumulation of hydrogen peroxide (H2O2), suggesting that MC-LR suppresses cell viability via oxidative damage. Furthermore, we found that MCs induced desulfhydrase (DES) activity for hydrogen sulfide (H2S) generation at the beginning stage. Additional H2S donors reactivated antioxidant enzyme activity, which reduced H2O2 accumulation and ultimately enhanced C. reinhardtii tolerance to MC-LR damage. This effect could be reserved by inhibiting H2S biosynthesis. Simultaneously, we found that H2S also suppressed MC-LR-induced cell autophagy, and thus attenuated the toxic effects of MC-LR. Our findings suggest that oxidative bursts may be the main reason for the allelopathic effects of MC-LR on C. reinhardtii viability and that H2S signaling may enhance C. reinhardtii tolerance to MC-LR through the activation of antioxidant enzyme activity and suppression of cell autophagy.